Cardiac Toxicity Under Concurrent Administration of Trastuzumab (Anti‐HER2 Therapy) and Radiotherapy: Systematic Review and Meta‐Analysis - Ali Jabbari; Elham Mousavi; Majid Nikoubin‐Boroujeni; Shabnam Tabasi; Nazila Arjmandi; Noura Ghelishli; Zahra Arab‐Bafrani (Health Science Reports)
ABSTRACT Background and Aims Concomitant administration of trastuzumab (Tra) and radiotherapy (RT) has been known as an effective strategy for treating HER2‐positive breast cancer (HER2+ BC) patients. Studies have investigated the incidence of cardiotoxicity due to this concomitant treatment, but the results are conflicting. This systematic review and meta‐analysis study evaluated the cardiac toxicity occurrence in patients undergoing Tra + RT. Methods A systematic review was conducted on the databases of PubMed, WOS, and Scopus up to 2024. The decline in left ventricular ejection fraction (LVEF) from baseline was assessed as a cardiac toxicity indicator, LVEF reduction Grade 1 (LVEF 60%–50%), Grade 2 (LVEF 50%–40%), and Grade 3 (LVEF 40%–20%). Results Seven studies meeting defined criteria were included in this investigation. This study examined the prevalence of LVEF‐grade 1–3 in HER2+ BC patients undergoing concurrent treatment with Tra and RT. The combined results showed a prevalence of decreased LVEF in Grades 1–3 as 21.4%, 4%, and 1%, respectively, with statistical significance (p < 0.05). Thus, among patients experiencing decreased LVEF, 70% were Grade 1, 25% were Grade 2, and 5% were Grade 3. Conclusion Cardiotoxic effects of chemotherapy and RT may accumulate and lead to heart failure so early diagnosis methods are advised. Concurrent RT with Tra is well‐tolerated clinically, and coadministration does not significantly raise primary cardiotoxicity. Cardiac toxicity may occur in some patients, requiring long‐term follow‐up to assess the impact of combining Tra and RT on heart function and its correlation with patient prognosis.